Economic relations between East and West : proceedings of a conference held by the International Economic Association at Dresden, GDR - Watts, Nita G. M.; International Economic Association (London : Macmillan, 1978)
This book is the outcome of the papers and discussions of the Dresden "Round Table" Conference.
Includes bibliographical references and index.
rpm 22/01/2019
Loans
Keywords: East-West trade; International economic relations